ICH Entrepreneurship Opportunties via Design Thinking, AI, and SDGs for 2030 - Yeung, Shirley MC (Sekolah Tinggi Manajemen IPMI, 2025)
The application of Halal concepts to the ICH, for example, traditional clothing (cheongsam) market for 2030 presents a business/ social opportunity for growth. By understanding Halal sustainability audit system with ISO Plan/ Do/ Check/ Act (PDCA) System - ethical sourcing and planning, doing in production of products/ services, and checking with design review, and acting with integrating AI for halal sustainability audit review and continual improvement in the traditional cheongsam service sector. S.E. countries may be a potential of ICH x AI market with creation of decent jobs (SDG#8) and nurture a mindset of SDG#3/#912/16 culturally rich, ethically sound, and truly sustainable with peace. This requires a conscious effort to bridge cultural understanding, embrace ethical practices, and leverage the power of tradition and innovation to groom future entrepreneurs in ICH with cultural beauty and halal responsibility.